PATHOPHYSIOLOGICAL AND CLINICAL ASPECTS OF THE CALCIUM DEFICIT AMONG CHILDREN. PRINCIPLES OF ITS PREVENTION - O.V. Stennikova; N.E. Sannikova ("Paediatrician" Publishers LLC, 2007)
The article analyzes the data on the physiological role of calcium, most significant risk factors for the phosphoccalci exchange disorders in the childhood, clinical manifestations of the calcium deficit. The authors also present the modern approaches to the prevention and correction of the micronutrient deficiency among children.Key words: children, calcium, exchange, deficit, prevention.